A Randomized Study of Rotigotine Dose Response on Off Time in Advanced Parkinson S Disease - Chana-Cuevas, P (2014)
BACKGROUND: Previous phase III studies in patients with advanced Parkinson s disease (PD) not adequately controlled on levodopa demonstrated significant reduction of off time with rotigotine transdermal system up to 16 mg/24 h. However, the minimal effective dose has not been established.OBJECTIVE: This international, randomized, double-blind, placebo-controlled study (SP921; NCT00522379) investigated rotigotine dose response up to 8 mg/24 h.METHODS: Patients with advanced idiopathic PD (?2.5 h of daily off time on stable doses of levodopa) were randomized 1:1:1:1:1 to receive rotigotine 2, 4, 6, or 8 mg/24 h or placebo, titrated over 4 weeks and maintained for 12 weeks. The primary efficacy variable was change from baseline to end of maintenance in absolute time spent off .RESULTS: 409/514 (80%) randomized patients completed maintenance. Mean (±SD) baseline daily off times (h/day) were placebo: 6.4 (±2.5), rotigotine 2-8 mg/24 h: 6.4 (±2.6). Rotigotine 8 mg/24 h was the minimal dose to significantly reduce off time versus placebo. LS mean (±SE) absolute change in daily off time (h/day) from baseline was -2.4 (±0.28) with rotigotine 8 mg/24 h, and -1.5 (±0.26) with placebo; absolute change in off time in the 8 mg/24 h group compared with placebo was -0.85 h/day (95% CI -1.59, -0.11; p = 0.024). There was an apparent dose-dependent trend. Adverse events (AEs) reported at a higher incidence in the rotigotine 8 mg/24 h group versus placebo included application site reactions, nausea, dry mouth, and dyskinesia; there was no worsening of insomnia, somnolence, orthostatic hypotension, confusional state or hallucinations, even in patients ?75 years of age.CONCLUSIONS: The minimal statistically significant effective dose of rotigotine to reduce absolute off time was 8 mg/24 h. The AE profile was similar to previous studies.